ANALISIS PENGARUH EKONOMI DIGITAL TERHADAP KEBERHASILAN USAHA PEDAGANG DAN UMKM: SYSTEMATIC LITERATURE REVIEW (SLR) - Intan, Kurnia; Kamalia, Putri Ulfa (Yayasan Education and Social Center, 2025)
A country's economy cannot be separated by one important sector, namely MSMEs or Small and Medium Enterprises. The development of the number of MSMEs that are not in line with the use of advanced technology can affect the level of income which is an important aspect in business success. This study aims to find out how the implementation of the digital economy affects the business success of business actors such as traditional market traders and other MSME actors. This study uses the SLR (Systematic Literature Review) method. Data collection is the result of searching for literature through reputable journals, then the researcher reviews the literature so that it gets appropriate research results. This study states that the positive implications of the digital economy are very broad for all MSME business actors. Studies show that there is a positive influence, where the development of the digital economy substantially increases the income of MSME actors which is an important aspect in Business Success. In the next research, it is hoped that it can expand the reach of research areas with different characteristics.